Flash Damage Expert System Using the Dempster Shafer Method - Yogi Bagus Arya (International Journal of Mechanical Computational and Manufacturing Research, 2023)
The rapid development of technology makes it easy to solve problems and get satisfactory results for the lives of many people. An expert system is a branch of artificial intelligence that is designed by embedding the knowledge of an expert in a computer. Expert systems can replace the role of an expert by using a computer that can provide definite solutions like an expert. In writing this thesis it is explained how a computer can detect damage from a flashdisk and the solution to the resulting damage like an expert using the Dempster Shafer calculation method. This expert system program is implemented using the Microsoft Visual Basic 2010 programming language with SQL Server 2008 database as the storage medium.